2006
DOI: 10.1080/09603120601093600
|View full text |Cite
|
Sign up to set email alerts
|

Food-associated bacteria in bioaerosols of delicatessens

Abstract: Air constituency of the delicatessen sections of a retail group was assessed for the presence and distribution of bioaerosols and the correlation with physical parameters. Total viable counts were determined and the total coliforms, Escherichia coli, other members of the Enterobacteriaceae and Staphylococcus aureus were enumerated. These counts were relatively low, with the average total viable counts 1.34x102 cfu . m-3, Enterobacteriaceae 2.6x10 cfu . m-3 and S. aureus 2.2x10 cfu . m-3. Small numbers of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These results were corroborated by three community-based studies [2125] in which airborne dispersal of pathogenic bacteria was identified in a university classroom, retail outlets, and office suites, and all studies recorded increased human movement as significant predictors of contamination. Notably, two of the retail outlet studies found the airborne bacterial load to be significantly related to the number of visitors attending the outlet [24, 25].…”
Section: Resultsmentioning
confidence: 99%
“…These results were corroborated by three community-based studies [2125] in which airborne dispersal of pathogenic bacteria was identified in a university classroom, retail outlets, and office suites, and all studies recorded increased human movement as significant predictors of contamination. Notably, two of the retail outlet studies found the airborne bacterial load to be significantly related to the number of visitors attending the outlet [24, 25].…”
Section: Resultsmentioning
confidence: 99%
“…Survey Methods. The survey questionnaire was made according to relevant literature which underwent repeatedly modifies and pre-survey modified form [3,5,6,8,9,10,11]. The questionnaire was included the basic information of the office workers, the place of eating out, awareness of food safety before and during eating out and food safety knowledge on eating out.…”
Section: Introductionmentioning
confidence: 99%